Speleothem‐Based Hydroclimate Reconstructions During the Penultimate Deglaciation in Northern China. Issue 4 (20th April 2021) - Xue, Gang; Cai, Yanjun; Lu, Yanbin; Ma, Le; Cheng, Xing; Liu, Chengcheng; Yan, Hong; Sun, Youbin; Li, Dong; Wei, Yingying; Huang, Shouyi; He, Mei; et al.
Abstract: Trace elements in a speleothem have been considered to be effective proxies to characterize hydroclimatic changes. In this study, we present speleothem trace element records of the penultimate glacial‐interglacial transition from 138 to 125.8 ka BP from the Shangxiaofeng cave in northeastern China. We used two analytical methods, namely, inductively coupled plasma optical emission spectrometry (ICP‐OES) and the Avaatech high‐resolution X‐ray fluorescence (XRF) core scanner. Both methods showed good consistency for Sr/Ca but not for Mg/Ca because of the high Mg detection limit of XRF. By comparing the trace element ratios (Sr/Ca and Mg/Ca) with δ 13 C and by analyzing the slope of the regression line of ln(Sr/Ca) versus ln(Mg/Ca), we found that trace element variations were dominated by hydroclimate‐related prior calcite precipitation (PCP) and water‐rock interaction (WRI). A gradually decreasing trend of Sr/Ca, Mg/Ca, and δ 13 C records during the glacial‐interglacial transition indicated that the hydroclimate moved toward a moist condition with an intensified East Asian summer monsoon (EASM) and transgression of the coastline. The transgression shortened the distance between the cave site and the coastline, possibly contributing to persistent rainfall enhancement at the study site. Key Points: The climate gradually turned wet during the penultimate deglaciation in Northern China Coastline regression could contribute to regional humidification during the deglaciation The X‐ray fluorescence measurement of Mg in stalagmites is not reliable and should be crosschecked